Introduction to the Special Section in "Geodynamics, Crustal and Lithospheric Tectonics, and Active Deformation in the Mediterranean Regions" (A Tribute to Prof. Renato Funiciello). Issue 7 (2nd July 2021) - Meghraoui, Mustapha; Jolivet, Laurent; Wortel, Rinus; Conticelli, Sandro
Key Points: New data and recent analysis of structural geology of the Mediterranean regions Introduction to "Geodynamics, Crustal and Lithospheric Tectonics, and active deformation in the Mediterranean Regions" A tribute to Prof. Renato Funiciello